The Expression and Survival Significance of Glucose Transporter-1 in Pancreatic Cancer: Meta-Analysis, Bioinformatics Analysis and Retrospective Study. (21st October 2021) - Du, Jiali; Gu, Jichun; Deng, Junyuan; Kong, Lei; Guo, Yujie; Jin, Chen; Bao, Yun; Fu, Deliang; Li, Ji
Abstract: To explore the expression profile and prognostic relevance of GLUT-1 in pancreatic cancer, a meta-analysis, bioinformatics analysis based on Gene Expression Omnibus (GEO), Oncomine dataset and The Cancer Genome Atlas (TCGA) database, and immunohistochemistry in tumor and normal tissue from 88 pancreatic ductal adenocarcinoma (PDAC) patients were performed. GLUT-1 was significantly overexpressed in pancreatic cancer but it could not be a significant biomarker for prognosis. TNM stage and pathological grade could be biomarker of poor prognosis of patients with pancreatic cancer.